The economic crisis and the return to farming in the Canaries - Carlos Santiago Martín Fernández; Víctor O. Martín Martín (Boletín de la Asociación de Geógrafos Españoles)
The crisis and the loss of population activates in subsectors as the construction and other partners to the services, has propitiated the return and incorporation of many workers to the primary activity. This return is carried out fundamentally out of the system of official control, turning into an economic irregular activity that nowadays it supports to many homes. The Administration, to avoid this situation, has carried out measures like the banks of lands and the urban gardens, which alone have supposed a partial solution to the poor familiar economies.